2018
DOI: 10.1007/s10571-018-0597-2
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-199a-5p Protects Spinal Cord Against Ischemia/Reperfusion-Induced Injury via Downregulation of ECE1 in Rat

Abstract: Ischemia-reperfusion (I/R)-induced spinal cord injury can cause apoptotic damage and subsequently act as a blood-spinal cord barrier damage. MicroRNAs (miRNAs) contributed to the process of I/R injury by regulating their target mRNAs. miR-199a-5p is involved in brain and heart I/R injury; however, its function in the spinal cord is not yet completely clarified. In this study, we investigated the role of miR-199a-5p on spinal cord I/R via the endothelin-converting enzyme 1, especially the apoptosis pathway. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 49 publications
1
41
1
Order By: Relevance
“…Thus, it participates in the metabolism of α-synuclein that could contribute to the development and progression of dementia with Lewy bodies. It is interesting to note that miR-199a-5p, which negatively regulated ECE1, and silencing the ECE1 gene are protected the rat spinal cord injury after ischemia-reperfusion (Bao et al 2018). Therefore, we demonstrated that miR-199a-5p might protect the spinal cord against ischemia-reperfusion-induced injury by negatively regulating the ECE1.…”
mentioning
confidence: 65%
“…Thus, it participates in the metabolism of α-synuclein that could contribute to the development and progression of dementia with Lewy bodies. It is interesting to note that miR-199a-5p, which negatively regulated ECE1, and silencing the ECE1 gene are protected the rat spinal cord injury after ischemia-reperfusion (Bao et al 2018). Therefore, we demonstrated that miR-199a-5p might protect the spinal cord against ischemia-reperfusion-induced injury by negatively regulating the ECE1.…”
mentioning
confidence: 65%
“…Lv et al reported that miR-199a can be sequestered by lncRNA-Map2k4, which subsequently promotes FGF1 expression and mouse spinal cord neuron growth 35 . Bao et al revealed that miR-199a-5p might protect the spinal cord against I/R-induced injury by negatively regulating ECE1 in rats 36 . These findings indicated that miR-199a plays different roles in various disease models.…”
Section: Discussionmentioning
confidence: 99%
“…We Several miRNAs are aberrantly expressed during spinal cord IR, and may act as protective or pathological factors. For example, increased levels of miR-27a attenuated IR-related damage in the spinal cord by targeting the TLR4 inflammatory pathway [24], while miR-199a-5p also exerted a protective effect by blocking ECE1-mediated apoptosis signaling [28]. In contrast, inhibiting miRNA-124 protected rats against spinal cord IR by inducing mitophagy [29].…”
Section: Discussionmentioning
confidence: 99%